2019
DOI: 10.3389/fphar.2019.01248
|View full text |Cite|
|
Sign up to set email alerts
|

Eupafolin Suppresses Esophagus Cancer Growth by Targeting T-LAK Cell-Originated Protein Kinase

Abstract: Eupafolin is the main bioactive component extracted from the traditional Chinese medicine Ay Tsao (Artemisia vulgaris L.), and its anti-tumor activity has had been studied in previous researches. T-LAK cell-originated protein kinase (TOPK) belongs to serine/threonine protein kinase and is highly expressed in several cancer cells and tissues, such as colon cancer, lung cancer, esophagus cancer, and so on. Therefore, it was recognized as an important target for treating tumors. Nowadays, we found that eupafolin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In the xenograft tumor formation assay, the expression of Cle-caspase was significantly elevated while Ki67 expression was drastically reduced by EV-delivered miR-375. Consistent with this, the downregulation of Ki67 and upregulation of Cle-caspase have been considered as important indicators for inhibited tumor growth [ 32 ]. Multiple studies have reported that miRNAs can be carried by BMSC-derived EVs and then play an inhibitory role in the pathogenesis of human diseases [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 78%
“…In the xenograft tumor formation assay, the expression of Cle-caspase was significantly elevated while Ki67 expression was drastically reduced by EV-delivered miR-375. Consistent with this, the downregulation of Ki67 and upregulation of Cle-caspase have been considered as important indicators for inhibited tumor growth [ 32 ]. Multiple studies have reported that miRNAs can be carried by BMSC-derived EVs and then play an inhibitory role in the pathogenesis of human diseases [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 78%
“…Nepetin, also known as Eupafolin or 6‐Methoxyluteolin, is a natural active flavonoid 30 . It has been confirmed to possess potent anti‐inflammatory effects as well as anti‐oxidant and anti‐tumorigenic effects 18,19,31 . Given Nepetin's diverse biological effects of Nepetin, we thus examined whether Nepetin can affect osteoclast formation and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…30 It has been confirmed to possess potent anti-inflammatory effects as well as anti-oxidant and anti-tumorigenic effects. 18,19,31 Given Nepetin's diverse biological effects of Nepetin, we thus examined whether Nepetin can affect osteoclast formation and bone resorption. In our study, Nepetin was found to potently shown that autophagy is important for bone homeostasis and is involved in the regulation of bone physiology and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Eupafolin alleviates cerebral ischemia/reperfusion injury in rats via blocking the TLR4/NF-ÎșB signaling pathway activation and also resulted in nuclear translocation (12). In addition, the suppressive effects of eupafolin on various tumor types, including esophageal cancer, hepatocellular carcinoma, renal carcinoma and prostate cancer has been extensively studied (13)(14)(15)(16). These data suggested the potential value of eupafolin in treating cancer and inflammation-related diseases.…”
Section: Introductionmentioning
confidence: 89%